Performance of anticorrosive coatings for photovoltaic PHC pipe piles in brine environments of saline-alkali tidal flats - Jianxin Wu; Jianyong Han; Jianyong Han; Yong Luo; Hongzhu Song; Hai Li; Xiaobin Dong (Frontiers in Earth Science)
This study was conducted on an integrated wind-solar-storage-transmission base project located in a saline-alkali tidal flat area. The brine formation mechanism in saline-alkali tidal flats was revealed, and the chemical composition of the brine was comprehensively characterized by on-site tests. The mechanisms and causes of corrosion of PHC pipe piles under brine exposure were revealed. Field tests of the surface morphology and thickness changes for four types of anticorrosion coatings applied to PHC pipe piles were conducted to determine the protective performance of each anticorrosion coating. The results show that PHC pipe pile corrosion in the brine environment of saline-alkali tidal flats is primarily driven by hydrogen ion erosion. After nearly 1 year of in situ corrosion testing, the surfaces of ZB, ZH, TD-D (double-sided application), and LC exhibited oxidation and darkening in color, with coating thickness reductions ranging from 0 to approximately 0.35 mm; however, the coatings remained largely intact. For the TD-S specimens (single-sided application), the coated surface darkened, whereas the uncoated surface experienced severe corrosion, with a thickness reduction of approximately 1.8 mm, accompanied by mortar spalling and coarse aggregate exposure. All four anticorrosive coatings demonstrated favorable protective performances. A comprehensive evaluation model was employed to grade and score the coatings based on three performance indicators, which revealed that the TD anticorrosive coating exhibited the best overall performance. This study provides essential scientific evidence and technical support for the durability design and protective measures of concrete structures under aggressive environmental conditions.